Sentence Structure Utilization in English Academic Writing Courses of Students in ELESP - Siti Safitri; Zulkifli Tanipu; Sri Widyarti Ali (Transbahasa, 2025)
This study investigates the Sentence structure utilization in English academic writing courses of students in ELESP. This study utilizes a descriptive qualitative method with a cross-sectional design to describe the sentence structure utilization between students from the 2020 and 2021 academic years. The results convey that students' command of sentence structures exhibits both promising aspects and areas requiring substantial improvement. The most prominent pattern observed is the heavy reliance on simple and compound sentences in academic writing tasks. Furthermore, the study has uncovered a significant correlation between sentence structure variety and sentence structure problems in their academic writing. However, many students tend to fall back on familiar patterns, resulting in monotonous writing that fails to effectively capture the nuances of academic argumentation. The findings reveal that students of both academic years could construct sentences, but were only able to compose simple and compound sentences when compiling their writing assignments. Therefore, this study provides pedagogical implications for academic writing students, underscores the development of students’ sentence structure competency, and the learning process to facilitate the students with the proper educational resources.